Autophagy in Parkinson's Disease. Issue 8 (3rd April 2020) - Hou, Xu; Watzlawik, Jens O.; Fiesel, Fabienne C.; Springer, Wolfdieter
Abstract: Impaired protein homeostasis and accumulation of damaged or abnormally modified protein are common disease mechanisms in many neurodegenerative disorders, including Parkinson's disease (PD). As one of the major degradation pathways, autophagy plays a pivotal role in maintaining effective turnover of proteins and damaged organelles in cells. Several decades of research efforts led to insights into the potential contribution of impaired autophagy machinery to α-synuclein accumulation and the degeneration of dopaminergic neurons, two major features of PD pathology. In this review, we summarize recent pathological, genetic, and mechanistic findings that link defective autophagy with PD pathogenesis in human patients, animals, and cellular models and discuss current challenges in the field. Graphical abstract: Image 1 Highlights: Dysregulations of different autophagy pathways in Parkinson's disease (PD) brain. Effects of PD-related genes on different autophagy pathways and impact of impaired autophagy on PD-related phenotypes. Synaptic homeostasis and autophagy in PD. Autophagy proteins as early PD biomarkers. Current challenges and future perspectives in the autophagy research in PD.